2016
DOI: 10.1177/0022034516634647
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 Impairs Salivary Tight Junction Integrity in Sjögren’s Syndrome

Abstract: Sjögren's syndrome (SS) is an inflammatory autoimmune disease that causes secretory dysfunction of the salivary glands. It has been reported that proinflammatory cytokine interleukin-17 (IL-17) was elevated and tight junction (TJ) integrity disrupted in minor salivary glands from SS patients. However, whether the elevated IL-17 in SS affects TJ integrity and thereby alters the function of salivary gland is unknown. Here, by using nonobese diabetic (NOD) mice as SS model, we found that the stimulated salivary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 32 publications
(37 reference statements)
4
36
0
Order By: Relevance
“…The expression and organization of TJ proteins are altered during several pathological processes of xerostomia (Ewert et al , 2010; Mellas et al , 2015; Ding et al , 2017; Cong et al , 2018; Zhang et al , 2019). In salivary glands of SS patients and NOD mice, the integrity of TJs is disrupted, including elevated Cldn1 and Cldn3 expression as well as reduced Cldn4, Ocln, and ZO‐1 expression (Zhang et al , 2016). ZO‐1 is also observed to be decreased in post‐irradiated human SMG (Nam et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression and organization of TJ proteins are altered during several pathological processes of xerostomia (Ewert et al , 2010; Mellas et al , 2015; Ding et al , 2017; Cong et al , 2018; Zhang et al , 2019). In salivary glands of SS patients and NOD mice, the integrity of TJs is disrupted, including elevated Cldn1 and Cldn3 expression as well as reduced Cldn4, Ocln, and ZO‐1 expression (Zhang et al , 2016). ZO‐1 is also observed to be decreased in post‐irradiated human SMG (Nam et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In hyposecretory SMG, acinar TJ width is decreased, while the expression of ZO‐1, Cldn3, and Cldn11 are reduced (Cong et al , 2012; Yang et al , 2017). Additionally, both epithelial and endothelial TJs are disrupted in salivary glands of patients with Sjögren's syndrome (SS) as well as model mice, contributing to salivary hyposecretion (Zhang et al , 2016; Cong et al , 2018). Moreover, TJs are reportedly damaged in other diabetes complications (Jiang et al , 2019; Bu et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 ] Recently, Rebuffat et al [ 31 ] showed that Tj protein – ZO-1, claudin-1, and JAM-A protein organization and expression as well as localization in the thyroid tissue of patients suffering from AITD are modified by proinflammatory cytokine IL-1β thus affecting thyroid epithelium integrity. Zhang et al [ 34 ] explored the signaling pathway that links IL-17 with Tj in salivary gland cell culture and postulated that IL-17 could directly modulate Tj protein expression and distribution through the NF-κB signaling pathway. To evaluate whether there is a relationship between IL-17 and Tj disruption, we did correlation analysis between the levels of IL-17 and Tj proteins expression in AITD patients, but no significant association with IL-17A was found.…”
Section: Discussionmentioning
confidence: 99%
“…Sjögren's syndrome (SS) as a chronic systemic autoimmune disease is characterized by mononuclear infiltration in the exocrine glands, which results in salivary and lacrimal gland functional impairment [1]. Immunocomplex deposition caused by B cell hyperactivity implies the underlying pathogenesis [2], and other immune cell abnormal activations also display an important pathogenic role in SS pathological processes [3,4]. Due to the complex syndrome of SS, clarifying the pathogenic mechanisms and improving the therapeutic strategy still are major challenges.…”
Section: Introductionmentioning
confidence: 99%